Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1063/1.442299
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of crystallization by homogeneous nucleation in a 4000-atom soft-sphere model

Abstract: A molecular dynamics simulation of crystallization by the process of spontaneous homogeneous nucleation fot a model of 4000 soft spheres with periodic boundary conditions is reported. When the amorphous system in the metastable state, at a point for which classical homogeneous nucleation theory predicts a vanishing of the free energy barrier, is annealed, many crystallites with variable symmetries are formed in the system. The nature and structures of the growing crystallites are analyzed by examination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 17 publications
1
37
0
2
Order By: Relevance
“…Nevertheless, a high degree of bcc ordering in the interface is retained. This may explain why in earlier simulations on small systems nucleation of a metastable bcc phase was observed, 3,[15][16][17] while in similar simulations on larger systems the formation of the fcc nuclei was observed. [18][19][20][21][22][23] In the smaller systems the critical nuclei will be so small that their structure is almost completely surface dominated, leading to a high degree of bcc ordering.…”
Section: B Summary Of Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, a high degree of bcc ordering in the interface is retained. This may explain why in earlier simulations on small systems nucleation of a metastable bcc phase was observed, 3,[15][16][17] while in similar simulations on larger systems the formation of the fcc nuclei was observed. [18][19][20][21][22][23] In the smaller systems the critical nuclei will be so small that their structure is almost completely surface dominated, leading to a high degree of bcc ordering.…”
Section: B Summary Of Resultsmentioning
confidence: 73%
“…[12][13][14] However, when the formation of metastable bcc nuclei was investigated on a microscopic scale using computer simulation, the picture that emerged was not fully in agreement with the Alexander-McTague scenario. Although in some studies nucleation of the metastable bcc phase was observed, 3,[15][16][17] most studies found evidence for the formation of the stable fcc phase. [18][19][20][21][22][23] Of particular interest is a simulation study by Swope and Andersen 23 of a one million particle Lennard-Jones system, which has a stable fcc phase below the melting line.…”
Section: A Backgroundmentioning
confidence: 99%
“…Even if the final result (a 3D model arrangement of like atoms) would be virtually the same as that obtained by DRPHS model building [12], quench simulation by molecular dynamics [15] or sequential atom addition to a selected seed [5,13,16], the DRPSU approach allows a more transparent description, in which different aspects (network topology, interconnection mode, structural unit) can be distinguished and treated separately. Moreover, other properties are easily recognized without the need to perform statistical analyses; thus, it is immediately clear that the structure is homogeneous, virtually isotropic and built from tetrahedra whose distortions (inherent to frustration [17], the impossibility to tile flat space with tetrahedra) are evenly distributed.…”
Section: Discussionmentioning
confidence: 98%
“…Now we turn to the bcc-fcc phase transition. Indeed, it has been reported long time ago that improper choice of particle number may mislead the resulted crystal structure due to the restriction of periodic boundary condition, especially when the simulation box is not large enough [30,31,23]. Under small system size, the particles are more readily to reach metastable bcc structures because there is a lower free-energy barrier for the formation of bcc crystallites from the melt, even though fcc is presumably the stable solid phase [25,29].…”
Section: Resultsmentioning
confidence: 99%